2016
DOI: 10.20882/adicciones.828
|View full text |Cite
|
Sign up to set email alerts
|

Consumo de krokodil por vía oral en España: a propósito de un caso

Abstract: The krokodil use disorder is an addictive pathology with quite severe organic effects, especially at the skin level, that causes severe and degenerative necrosis of blood and muscle tissue. Though this disorder has a low prevalence in Spain, compared to the large number of consumers in other countries such as Ukraine or Russia, its consumption is slowly but gradually expanding in countries of the European Union and America. The simplicity of the process of obtaining the substance from desomorphine, together wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…Concerning the influence on soft-tissues, Haskin et al, reported extended, non-healing, necrotic skin wounds on the legs after long-time desomorphine abuse [ 24 ]. Baquero Escribano et al, described also that desomorphin is able to induce skin wounds and skin necrosis and further necrosis of blood and muscle tissues [ 25 ]. This might lead to the assumption that methamphetamine-induced osteonecrosis of the jaws might be caused or triggered by methamphetamine’s influence on soft-tissues and vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the influence on soft-tissues, Haskin et al, reported extended, non-healing, necrotic skin wounds on the legs after long-time desomorphine abuse [ 24 ]. Baquero Escribano et al, described also that desomorphin is able to induce skin wounds and skin necrosis and further necrosis of blood and muscle tissues [ 25 ]. This might lead to the assumption that methamphetamine-induced osteonecrosis of the jaws might be caused or triggered by methamphetamine’s influence on soft-tissues and vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Since its appearance in Russia, the drug quickly spread to other neighboring former Soviet republics, especially Ukraine (which had around 20 000 cases in 2011), , as well as Georgia, Armenia, , and Kazakhstan. , The first western European country to report cases of krokodil use was Germany in 2011 . Subsequently, cases (both confirmed and suspected) have been reported in other European countries, such as France, Italy, Norway, Spain, and Poland, , with a significant part of them imported from Eastern Europe through immigrants from former Soviet republics . It is noteworthy that various reviews mention cases reported in the Czech Republic, Sweden, Belgium, and Portugal, ,,, but reliable information about these cases could not be found by the authors of the current review.…”
Section: Desomorphine (Krokodil)mentioning
confidence: 99%
“…Just like heroin and many other opioids, desomorphine is administered intravenously (the most common route), intramuscularly, and subcutaneously, ,, although oral administration has also been reported . The reported harms caused by the drug’s administration can be local, systemic, and neurological (Table ).…”
Section: Desomorphine (Krokodil)mentioning
confidence: 99%
See 1 more Smart Citation
“…La molécula del krokodil, muy similar a la de la morfina, es un potente µ-opioide con gran toxicidad y un poder analgésico 5 a 10 veces mayor que el de la morfina; se sintetiza a partir de la codeína combinada con otros aditivos de fácil obtención y bajo costo. El neologismo krokodil (del ruso cocodrilo) se originó a partir de la apariencia de piel de cocodrilo que pueden presentar los consumidores, con piel verdosa oscura y con descamación (4,5) . Con el diagnóstico clínico-patológico de vasculitis por consumo de cocaína adulterada, posiblemente con levamisol, se inició el tratamiento.…”
Section: Caso Clínicounclassified